Alstonia scholaris Linn. R. Br.: An Assessment of its Botany, Conventional Utilizaton, Phytochemistry and Pharmacology - Chhajed, Mahavir; Jain, Atika; Pagariya, Ashish; Dwivedi, Sumeet; Jain, Neetesh; Taile, Vijay (Pharmacognosy Reviews)
Alstonia scholaris, a plant that belongs to the Apocynaceae family and is widely used around the world, exhibits pharmacological properties that are advantageous to human health. It is a widely used plant that has been used in traditional medicine for a very long time. Rheumatism, antileprosy, ulcer, antiseptics, different chronic inflammatory skin conditions, rheumatoid arthritis discomfort, broad-spectrum tonic, antidysentery, and vulnerary agents have all been successfully treated with A. scholaris. Along with treating fatigue, antipyretic, anticholeric, malaria fever, irregular and unbalanced menstruation, hepatic problems, diabetes, and dysentery, it has also been beneficial in treating these other conditions. It possesses astringent, analgesic, anti-inflammatory, and anti-diabetic effects. Additionally, it has cytotoxic, radioprotective CNS, anti-arthritic, anti-cancer, antioxidant, anti-malarial, and anti-cancer effects. The numerous derivative metabolites were taken into account in the pioneering research on phytochemical analysis from the various plant sections. The plant displayed an abundance of metabolites, including tocopherols, polyunsaturated fatty acids, carboxylic acids, proteins, and carbohydrates. With a variety of biological functions, it also shown pharmaceutical efficacy. This evaluation seeks to acquaint the reader with the plant by adding to a clear overview of the botanical distinctiveness, typical uses, phytochemistry, and biological and pharmacological activities.
Keywords: A. scholaris; Traditional medicine; Phytoconstituents